2011
DOI: 10.2355/isijinternational.51.1755
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Time in a Cylindrical Bath Agitated by Gas Injection through an L-shaped Top Lance in the Absence of Swirl Motion

Abstract: Experimental investigations are carried out on mixing time in a water bath agitated by side gas injection with an L-shaped lance. The mixing time is measured using an electrical conductivity sensor and an aqueous KCl solution as a tracer. Particular attention is paid to bath agitation under the conditions that any kinds of swirl motions of a bubbling jet do not appear. An empirical equation is proposed for the mixing time as a function of the gas flow rate, bath diameter, bath depth, and the physical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Wang et al [10] found that the air flow rate and lance submergence depth can significantly influence the liquid mixing process and the liquid phase temperature field distribution, which provides a theoretical support for the operation of the furnace. The influencing factors of mixing time in submerged top-blow process were studied by water model experi-ment [11][12][13][14][15][16][17], it can be concluded that air flow rate, molten bath depth, lance submergence depth and inner diameter of the lance are the main influencing factors. Previous studies are significant, but lack of intuitive description of liquid mixing behavior and barely research on local mixing behavior in experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [10] found that the air flow rate and lance submergence depth can significantly influence the liquid mixing process and the liquid phase temperature field distribution, which provides a theoretical support for the operation of the furnace. The influencing factors of mixing time in submerged top-blow process were studied by water model experi-ment [11][12][13][14][15][16][17], it can be concluded that air flow rate, molten bath depth, lance submergence depth and inner diameter of the lance are the main influencing factors. Previous studies are significant, but lack of intuitive description of liquid mixing behavior and barely research on local mixing behavior in experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Argon-stirred ladles are commonly used in the secondary refining [1] to homogenize chemical compositions and the temperature [2][3][4][5] , to remove inclusions, [6,7] and to enhance the slag-metal reactions. [8][9][10] Many publications have been done to investigate the mixing phenomena in argonstirred ladles experimentally [11][12][13][14][15][16][17][18][19][20][21][22] and numerically, [23][24][25][26][27][28][29][30][31][32][33][34] but less of them coupled the melting of alloy particles.…”
Section: Introductionmentioning
confidence: 99%
“…Water modeling [11][12][13][14][15][16][17][18][19][20][21][22] was usually adopted to study the hydrodynamics and mixing phenomena in gas stirred ladles. Murthy and Elliott [12] examined the definition of mixing time and analyzed the reported concentration vs. time traces to determine mixing time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems can readily be solved when a top lance is used. In previous papers 4,5) the authors proposed a method of side gas injection through an L-shaped top lance and carried out water model experiments on the occurrence condition of a swirl motion of the deep-water wave type and on mixing time, Tm. First, the exit of the L-shaped top lance was placed on the centerline of a cylindrical vessel containing de-ionized water.…”
Section: Introductionmentioning
confidence: 99%